2011
DOI: 10.1007/s00170-011-3594-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of using different type of inlet vents on the thermal characteristics of the automobile cabin and the human body during cooling period

Abstract: A three-dimensional (3-D) transient numerical analysis was performed inside an automobile cabin during cooling period. A three-dimensional vehicle cabin including glazing surfaces was modelled by using the real dimensions of a car. A virtual manikin with real dimensions and physiological shape was added to the model of the vehicle cabin, and it was assumed that the manikin surfaces were subjected to constant temperature. The virtual manikin was divided into 17 parts in standing posture to evaluate the local he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The Reynolds number at the exit of the central air vents based on stream wise mean velocity and on the equivalent diameter (De 1 = 0.093m) was Re 1 = 17800, and for the side air vents Re2=14000 (De2= 0.073m). The inlet turbulence intensity was imposed for all vents as 4.11%, being calculated using the empirical relation proposed by Jaramillo [13]. For the left side air vent, we modified the angle of the vertical guiding vanes in the horizontal plane from 0° to 30°, with a 5° step angle.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reynolds number at the exit of the central air vents based on stream wise mean velocity and on the equivalent diameter (De 1 = 0.093m) was Re 1 = 17800, and for the side air vents Re2=14000 (De2= 0.073m). The inlet turbulence intensity was imposed for all vents as 4.11%, being calculated using the empirical relation proposed by Jaramillo [13]. For the left side air vent, we modified the angle of the vertical guiding vanes in the horizontal plane from 0° to 30°, with a 5° step angle.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The results showed that for the same initial conditions a round shape vent might be more efficient than regular square or elliptical vents, leading to a lower mean air temperature and to a better distribution of air velocity and temperature, under certain circumstances. The effects on thermal sensation of different positions of the air vents inside the passenger car were also numerically investigated by Kilic [13]. Three different positions, for the same cooling power, were analyzed under transient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In their numerical study, they developed a three dimensional CFD model of the vehicle cabin with an only driver inside and used the velocity and temperature values obtained from their experimental study. They also examined the effect of using different boundary conditions defined on human body surfaces to evaluate the thermal comfort [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, with more stringent requirements for efficient utilisation of energy resources within the transport industry must rely on improving energy efficiency of vehicles [1,2]. Computational fluid dynamics (CFD) analysis tool is now being used to evaluate the different environmental conditions of an automobile cabin in many aspects [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The need to reduce heat loads that enter passenger compartments has become an important issue in the early stage of vehicle design and the radiation plays an important role on the thermal comfort in the compartment [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The need to reduce heat loads that enter passenger compartments has become an important issue in the early stage of vehicle design and the radiation plays an important role on the thermal comfort in the compartment [3,4]. For these reasons described, CFD method is a useful tool to determine 3-D velocity and temperature distributions, thermal characteristics of the automobile cabin, and the local heat transfer characteristics of the surfaces of the human body [16,17]. Computational fluid dynamics (CFD) analysis tool is now being used to evaluate the different environmental conditions of an automobile cabin in many aspects [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%